Instruction in a holistic approach to discrimination (Academic Journal of Internal Affairs, 2020)
Administrative activity is present in all walks of life and it has a universal character nowadays. This article has been tabled to draw attention to the discriminatory erosions that sometimes appear as a hiding place in public administration, which may appear as minor deviations in childhood, but may lead to disintegration of organizational unit in adulthood. On the other hand, however, the quality of life of workers is impaired because workers exposed to psychosocial risks show significantly higher levels of health risk than those who are not. The most common symptoms are stress, sleep problems, fatigue and depression (URL1). I have tried to approach the relationship between instruction and discrimination holistically, from the slightest socialization error of man to the most serious crime. I believe that a person's discriminatory behavior is characterized by the inclusion of the milder deviations of a person to the more serious ones. Genocide certainly involves its four milder stages, the physical assault transmission, discrimination, verbal expression, and discriminatory thought. We have drawn attention to the harmful effects of ’invisible’ in its form, but abnormal in its content. Perhaps avoidance is one of the most insidious behaviors of our time, which, by distorting personality in childhood, can put its mark on the daily life and public service of an adult. In the case of discrimination, sanctions of a non-legal nature which undermine the offender's social authority may also be significant, e.g. mocking, exasperation, appearance, speaking, which are more common than legal sanctions and can cause a great deal of torment to the perpetrator and his environment, we need anti-instructional discrimination in the public sector to ensure good public services and well-being of public service employees. In the bureaucratic system, it is precise regulation that can be used to combat discrimination by instruction, because it not only serves to coordinate and fix the best method, but also ensures standardized, equal treatment of individual cases (Gajduschek, 2000, 44.). It is also worth noting that enforcing the prohibition of discrimination, its principles, its loyalty, impartiality, responsibility or professionalism, and the confidence of users of public services in the public service is in the interests of professional administration.
Keywords: instruction; discrimination; law; public sector